Displaced Workers in the United States and the Netherlands - Jaap H. Abbring; Gerard J. van den Berg; Pieter A. Gautier; A. Gijsbert C. van Lomwel; Jan C. van Ours; Christopher J. Ruhm (Tinbergen Institute, 1998)
This discussion paper has resulted in chapter 2 in: 'Losing Work, Moving On: International Perspectives On Worker Displacement', Peter J. Kuhn, Ed., 2002, W.E. Upjohn Institute for Employment Research, Kalamazoo, MI, ISBN 0-88099-234-4.
Keywords: 330; Arbeitslosigkeit; USA; Niederlande